DNA Computing for Solving Distribution Center Location Problem - Hasudungan, Rofilde; Rohani, Abu Bakar (2013)

(untitled)
Determination of distribution center location is one of importance issue in supply chain management since this problem affect to production cost and product flow. Nerveless, to choose appropriate the distribution center is not easy task, need to consider the best layout where we have to choose the appropriate number of distribution center and its position among all candidates, this make the determination distribution more complicated cause involving combination configuration. In this study, we proposed DNA computing to solve this problem since the advantages this technique is fall into huge massive parallelism.